Encourage Students’ Affective Value in EFL Class Through Cooperative Learning - Rabi'ah, Rabi'ah; Baidawi, Achmad; Hanna, Ina Daril (Lingual Journal of Language and Culture, 2021)
In this modern era, education is required not only to be able to create intelligent students but also to be able to create students who have good attitudes. The attitude that is needed when they are in the midst of society. Such as tolerance, respect for the opinions of others, mutual cooperation and the others. Considering that these attitudes have begun to decrease by the times and the advancement of civilization. Therefore, an educator is expected to be able to develop the ability of students not only in the cognitive domain but also in the affective domain. In this case, the lecturer as educator can give directly positive suggestion or creating a good teaching and learning that contain some valuable meaning. Implementing cooperative can covered both cognitive aspect and affective aspect. The method of study is qualitative approach which descriptive design.This paper aims to describe what attitudes can be developed by applying cooperative learning methods and what strategies in cooperative learning can be done to encourage affective values ??of students. To Achieve the aims of this study, the researcher conducts the research in State Islamic Institute of Madura (IAIN Madura). The subject is the students of English department in the first semester.The result showed that cooperative learning can improve respect, tolerate and solidarity value of the students. The model of cooperative learning that create those values are Number Head Together . Jigsaw , and Think Pair-share